Strategic orientation and its relationship to scientific methods for dealing with crises: A study of the opinions of administrative leaders at the Presidency of Sulaimani Polytechnic University - محمد, نیگا علي (Sulaimani Journal for Humanities, 2019)
This research was conducted to measure the relationship between scientific methods for facing the crises through its elements (the initial study dimensions of the crisis-the analytical study of the crisis-scientific planning to deal with the crisis) and strategic direction with its elements (vision, mission, goals, and values), in this research, we depended on the analytical descriptive approach and to achieve this goal, the (research tool) was used through a questionnaire form which was prepared specifically for this purpose and (65) forms were distributed among the administrative leaders at (Sulaymaniyah Polytechnic University) and (51) forms were returned which were useful for analyzing . In this research, two major hypotheses were formulated which includes the link correlation and influence between the two variables. The research found that there is a noticeable interest by the heads of administrators working in the presidency of the University of Sulaymaniyah in the scientific methods of dealing with crises and attention to the strategic direction processes. The existence of strategic directions of the organization (vision, message, values, and goals) has a positive relationship with the crisis management styles in the organization. The organization should continue to form an operations room equipped with the required and modern crisis management techniques to facilitate the communication process .
Keywords: Strategic approach to crisis management; scientific methods for confronting crises